Analisis Pengelolaan Keuangan pada UMKM di Kota Batam - Khadijah Khadijah; Neni Marlina Br Purba (Politeknik Ganesha Medan, 2021)
MSMEs are the main pillars of the Indonesian economy. One of the obstacles faced by MSMEs today is the number of MSMEs opening businesses with the same type of products. The purpose of this research is to be able to analyze financial management in MSMEs in Batam City. So that it can develop and be consistent with the effort. The method used is a qualitative descriptive method with a sample of 5 MSMEs namely Toko Pakaian Cantik, Toko Gamis Taqeeya, Toko Ringan, Toko Fashion Muslim, Toko Fathia Collection are in the type of trading industry with criteria still active and willing to conduct interviews on their business. The results of the study in accordance with 4 indicators in financial management showed that the overall MSMEs studied using planning in the use of budgets, making simple recordings, and using sufficient control. However, not all MSMEs understand the reporting indicators in business financial statements.